Evaluation of Ruta graveolens Extract as a Natural Fungicide against Alternaria alternata - أ. بوبكر سليمان الزحاف; د. غزالة ابراهيم فضيل (African Journal of Advanced Pure and Applied Sciences, 2026)
This study was conducted at the Department of Plant Production Technology, Higher Institute of Agricultural Technologies, Derna, to evaluate the inhibitory effect of Ruta graveolens leaf extract on the biological growth of Alternaria alternata, the causal agent of Alternaria leaf spot disease on citrus leaves. The results, obtained by applying the inhibition percentage equation, revealed significant differences among treatments in terms of mean inhibition rates. The highest inhibition percentages were recorded in the nano-formulated treatments, followed by the other treatments in suppressing the germination of Alternaria alternata. The nano alcoholic extract exhibited an inhibition rate of 84.29%, while the nano aqueous extract showed an inhibition rate of 78.87%, compared with the other treatments that resulted in lower inhibition percentages. Statistical analysis using analysis of variance (ANOVA) at a significance level of 0.05 indicated significant differences between the treatments and the control. However, no significant differences were observed between the aqueous and alcoholic extracts. Overall, the nano-formulated treatments demonstrated a higher inhibitory effect compared to the other treatments.